Heterosis for yield and quality traits in traditional and evolved Basmati - Jaiswal, Hemant Kumar; Sharma, Aarti (ORYZA-An International Journal of Rice, 2022)
A study was undertaken on 36 F1s obtained from diallel (without reciprocals) mating design to explicate the genetic behavior of traditional and evolved basmati varieties for 14 traits. F1s were divided into traditional x traditional (T x T); evolved x evolved (E x E) and traditional x evolved (T x E) basmati types; amidst which E x E and T x E type of crosses exhibited high positive average heterosis in comparison to T x T type of crosses for yield per plant trait. Assessment of quality traits for average heterosis indicated that, all the three types of crosses were equally effective for KL, KB and LBR. Manifestation of average heterosis for KLAC was better in TxT type as none of the ExE type of crosses showed significant positive heterosis; likewise, among 20 T x E type of crosses only 3 crosses showed significant positive heterosis. Heritability in narrow sense was high for: MPL, 100-GW, NGP, YPP, KL, LBR, and KLAC.